PENGARUH PERSEPSI KEMUDAHAN, KEBERMANFATAAN, RISIKO DAN KEPERCAYAAN TERHADAP MINAT NASABAH MENGGUNAKAN INTERNET BANKING PADA PT BANK BUKOPIN Tbk BANJARMASIN - Ruslinda Agustina; Rizki Amalia Afriana; Arisa Safrina (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2018)
Abstract, The purpose of this study is to prove empirically whether there is an effect of perceived ease, usefulness, risk and trust in the interests of customers using internet banking at PT Bank Bukopin, Tbk Banjarmasin. The sampling technique uses incident sampling, by distributing questionnaires to customers who incidentally meet with researchers as many as 73 respondents who use internet banking in November and December 2017. Processing with the help of SPSS version 16 test equipment. The results showed that perceptions of usefulness affect the interests of customers using internet banking, this is because customers assume that using internet banking has benefits so that customers are interested in using the internet banking. While perceptions of ease, risk and trust do not affect the interests of customers to use bankint's internet, this is because customers feel that it is not easy and less understandable to use internet banking, then customers feel that using internet banking has no risk and can provide good information for customers, and there is a sense of customer concern in using internet banking so that customers do not trust to use the internet banking.